Neonatal Brachial Plexus Palsy: Risk Factors and Its Prognostic Value - Ataíde, S (2019)
Introduction: Neonatal brachial plexus palsy affects 0.7 to 5.8 per 1,000 newborns and is characterised by upper limb paresis detected in the immediate neonatal period. Shoulder dystocia, instrumental delivery and foetal macrosomia are well-known risk factors. Most neonatal brachial plexus palsy evolve favourably, while 3%-27% of newborns have sequelae. Methods: A retrospective cross-sectional study was conducted to characterise neonatal brachial plexus palsy in the newborn population of a hospital with differentiated perinatal support and to assess the rela - tionship between the risk factors and lesion prognosis. The authors reviewed the newborn medical records referred to the physical medicine and rehabilitation clinic between January 2006 and December 2016. Results: During the study period, 137 cases of neo- natal brachial plexus palsy were identified in 36,833 births, which translate into an incidence of 3.7/1,000 live births. Foetal macrosomia was found in 41% and shoulder dystocia in 40%. According to the Narakas clas- sification, 58% were included in group I, 30% in group II, 9% in group III and 3% in group IV. The majority of patients were discharged without sequelae. Newborns with group II, III and IV lesions as well as macrosomic newborns were more likely to develop sequelae (p < 0.05). Shoulder dystocia and operative delivery did not present a statistically significant relationship with the prognosis of the lesion. Discussion: The incidence of neonatal brachial plexus palsy in this population was similar to is described in other series. The relationship between macrosomia and neonatal brachial plexus palsy with sequelae found may be of importance in the attempt to prevent this lesion